Plasma Lipidome, PNPLA3 polymorphism and hepatic steatosis in hereditary hemochromatosis - Seeßle, Jessica; Gan-Schreier, Hongying; Kirchner, Marietta; Stremmel, Wolfgang; Chamulitrat, Walee; Merle, Uta (BMC gastroenterology, 2020)
Hereditary hemochromatosis (HH) is an autosomal recessive genetic disorder with increased intestinal iron absorption and therefore iron Overload. iron overload leads to increased levels of toxic non-transferrin bound iron which results in oxidative stress and lipid peroxidation. The impact of iron on lipid metabolism is so far not fully understood. The aim of this study was to investigate lipid metabolism including lipoproteins (HDL, LDL), neutral (triglycerides, cholesterol) and polar lipids (sphingo- and phospholipids), and PNPLA3 polymorphism (rs738409/I148M) in HH.
Gesehen am 25.08.2020